2018
DOI: 10.3991/ijim.v12i7.9644
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Smart Board to Overcome Higher Order Thinking Skills Learning Difficulties in Data Handling among Primary School Students

Abstract: Data Handling at primary school involves gathering and recording information and then presenting it in a way that is meaningful to others. It is a fundamental part of student's mathematical understanding. Initial concepts of Data Handling need to be exposed to students in the early years as these skills will be used and built upon throughout their education. Due to its importance, Data Handling is included in the curriculum at primary level in Malaysia. However results of international assessments which focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The developed comic media can help improve the discipline character of grade IV students of Alquran Elementary School in a "moderate" rate of increase. More interactive technology tools can be used by elementary school students that can increase student motivation, student involvement in learning and ultimately can generate student learning interest [20]. On the other hand, active learning techniques can result in storing material in students' brains up to 90% so that it can be assumed that learning runs effectively [21].…”
Section: Description Of Product Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed comic media can help improve the discipline character of grade IV students of Alquran Elementary School in a "moderate" rate of increase. More interactive technology tools can be used by elementary school students that can increase student motivation, student involvement in learning and ultimately can generate student learning interest [20]. On the other hand, active learning techniques can result in storing material in students' brains up to 90% so that it can be assumed that learning runs effectively [21].…”
Section: Description Of Product Trialmentioning
confidence: 99%
“…More interactive technology tools can be used by elementary school students that can increase student motivation, student involvement in learning and ultimately can generate student learning interest [20]. On the other hand, active learning techniques can result in storing material in students' brains up to 90% so that it can be assumed that learning runs effectively [21]. Digital learning comic is packaged in the system of a DVD (Digital Video Disc) and the contents include: 1) Learning objectives, 2) Characters in comics, 3) Colored digital images, 4) Music accompaniment Effect, 5) Cartoon image format, 6) Image sequence of a story, 7) Narration that is packaged in balloon text, and 8) Type of font such as Arial, Comic and Sans.…”
Section: Description Of Product Trialmentioning
confidence: 99%
“…Research showed that high order thinking skills could be facilitated by using smart education. Julius proved that using the smart board can overcome high order thinking skills learning difficulties under the assistant of effective learning strategies (Julius et al, 2018). While smart devices cannot ensure the improvement of thinking ability, technology and pedagogy need to be combined in smart education.…”
Section: Introductionmentioning
confidence: 99%
“…Data handling plays an important role in mathematics education, because it covers real-life situations and helps students to develop their critical thinking skills (Reys, Lindquist, Lambdin and Smith, 2009). Data handling is a mathematics compound that is using mathematical tools to collect, organize, represent and interpret mathematical data to solve real-life issues Julius, Mun, Abdullah, Mokhtar and Suhairom, 2018). Data handling, statistics and probability provide a meaningful context to encourage problem solving and critical thinking, develop communication and the sense of digits and help in calculation activities (Reys, Lindquist, Lambdin and Smith, 2009).…”
Section: Data Handlingmentioning
confidence: 99%
“…Data handling constitutes an integral part of students' mathematical understanding. Students need to be introduced to the concept of data handling at an early age, because they will be using and developing this skill throughout their school life (Julius, Mun, Abdullah, Mokhtar and Suhairom, 2018).…”
Section: Data Handlingmentioning
confidence: 99%